STAT3 Modulation of Regulatory T Cells in Response to Radiation Therapy in Head and Neck Cancer. (13th March 2019) - Oweida, Ayman J; Darragh, Laurel; Phan, Andy; Binder, David; Bhatia, Shilpa; Mueller, Adam; Court, Benjamin Van; Milner, Dallin; Raben, David; Woessner, Richard; Heasley, Lynn; Nemenoff, Raphael; et al.
Abstract: Background: Radioresistance represents a major problem in the treatment of head and neck cancer (HNC) patients. To improve response, understanding tumor microenvironmental factors that contribute to radiation resistance is important. Regulatory T cells (Tregs) are enriched in numerous cancers and can dampen the response to radiation by creating an immune-inhibitory microenvironment. The purpose of this study was to investigate mechanisms of Treg modulation by radiation in HNC. Methods: We utilized an orthotopic mouse model of HNC. Anti-CD25 was used for Treg depletion. Image-guided radiation was delivered to a dose of 10 Gy. Flow cytometry was used to analyze abundance and function of intratumoral immune cells. Enzyme-linked immunosorbent assay was performed to assess secreted factors. For immune-modulating therapies, anti–PD-L1, anti-CTLA-4, and STAT3 antisense oligonucleotide (ASO) were used. All statistical tests were two-sided. Results: Treatment with anti-CD25 and radiation led to tumor eradication (57.1%, n = 4 of 7 mice), enhanced T-cell cytotoxicity compared with RT alone (CD4 effector T cells [Teff]: RT group mean = 5.37 [ 0.58] vs RT + αCD25 group mean =10.71 [0.67], P = .005; CD8 Teff: RT group mean = 9.98 [0.81] vs RT + αCD25 group mean =16.88 [2.49], P = .01) and induced tumor antigen-specific memory response (100.0%, n = 4 mice). In contrast, radiation alone or when combined with anti-CTLA4 did not lead to durable tumor control (0.0%, n = 7 mice). STAT3 inhibition in combination with radiation, but not as a single agent, improved tumor growth delay, decreased Tregs, myeloid-derived suppressor cells, and M2 macrophages and enhanced effector T cells and M1 macrophages. Experiments in nude mice inhibited the benefit of STAT3 ASO and radiation. Conclusion: We propose that STAT3 inhibition is a viable and potent therapeutic target against Tregs. Our data support the design of clinical trials integrating STAT3 ASO in the standard of care for cancer patients receiving radiation.